Analisis Transaksi Jual Beli Kelapa Sawit Ditinjau dari Perspektif Etika Bisnis Islam (Studi CV Rimbo Jaya Desa Perintis Makmur Kecamatan Rimbo Bujang Kabupaten Tebo) - Kurniawan, Dandi; Mubyarto, Novi; Rohana, Rohana (Lembaga Yasin AlSys, 2024)
This study aims to analyze how the sale and purchase of oil palm transactions are viewed from the perspective of Islamic business ethics that occur at CV Rimbo Jaya The main problems are put into several sub-problems or research questions, namely: 1. How is the palm oil sale and purchase transaction system at CV Rimbo Jaya. 2. How is the perspective of Islamic business ethics on oil palm buying and selling transactions at CV Rimbo Jaya, Perintis Makmur Village. This study aims to determine the reality of oil palm buying and selling transactions at CV Rimbo Jaya, Perintis Makmur Village. The method used in writing this thesis is descriptive qualitative method, using data collection techniques with Observation, Interview, and Documentation. The results of the research obtained regarding the sale and purchase of oil palm transactions carried out by toke and farmers. However, the problem that occurs is that there is fraud in weighing the oil palm sale and purchase transactions carried out by the toke to the farmers at CV Rimbo Jaya, Perintis Makmur Village. Cheating in weighing can be of special concern in the Koran because activities like this have deprived other people of their property rights.